Equity-Oriented Conceptual Framework for K-12 STEM literacy - Christa Jackson; Margaret J. Mohr-Schroeder; Sarah B. Bush; Cathrine Maiorca; Thomas Roberts; Caitlyn Yost; Abigail Fowler (SpringerOpen, 2021)
Abstract We introduce a conceptual framework of K-12 STEM literacy that rightfully and intentionally positions each and every student, particularly minoritized groups, as belonging in STEM. In order to conceptualize the equity-based framework of STEM literacy, we conducted a systematic review of literature related to STEM literacy, which includes empirical studies that contribute to STEM literacy. The literature on the siloed literacies within STEM (i.e., science, technology, engineering, and mathematics literacy) also contributed to formulate the necessity of and what it means to develop STEM literacy. The Equity-Oriented STEM Literacy Framework illuminates the complexities of disrupting the status quo and rightfully transforming integrated STEM education in ways that provide equitable opportunities and access to all learners. The Equity-Oriented STEM Literacy Framework is a research-based, equity and access-focused framework that will guide research, inform practice, and provide a lens for the field that will ensure each and every student, especially minoritized students, develop, and are developing STEM literacy.